PERSEPSI SISWA 4 SMA TERHADAP 2 SEKOLAH TINGGI EKONOMI DAN FAKULTAS EKONOMI DI KOTA JAMBI - Riko Mappedeceng (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Each Higher education must have a desire to be considered as the best among the other universities, not to mention the three Colleges in the city of Jambi, namely STIE Ikabama, STIE Muhammadiyah and the University of Batanghari. In this regard the student assessment of the status of the course, the image of Higher Education, available facilities, faculty quality, weight/lecture material and others have an important role in shaping students' perception of certain universities.Results of the study revealed that consumer behavior (in this case the students of SMAN 4, SMAN 10, SMAN 11, and SMA Adhyaksa I Jambi) in selecting and determining a college influenced the lecture material, the status of the course and the amount of tuition. This perception is formed through the information they obtain directly through friends (51.3%), family (37.3%), and from school each (5.3%). All respondents surveyed (ie 400 people) said their most important interest is in the field of economic studies (52.8%), engineering (30.3%) and tourism/hospitality (5%). As for the field of study of economics, management is the most preferred courses (59.7%), accounting (34.1%) and the Economics of Development Studies (6.2%), and the results of this study also note that students who want to go field of study economics, Faculty of Economics, University of Batanghari chose as the main option (38.4%), STIE Muhammadiyah as the 2nd option (14.2%), and STIE Ikabama as the 3rd option (12.8%).Key Word: University of Batanghari, STIE Muhammadiyah, STIE Ikabama